EMS Provider Perceptions on Termination of Resuscitation in a Large, Urban EMS System. (3rd September 2017) - Tataris, Katie L.; Richards, Christopher T.; Stein-Spencer, Leslee; Ryan, Stephanie; Lazzara, Pete; Weber, Joseph M.
ABSTRACT: Objective : Despite the value of out-of-hospital Termination of Resuscitation (TOR) and the scientific evidence in favor of this practice, TOR has not been uniformly adopted or consistently practiced in EMS systems. Previous focus group studies have identified multiple barriers to implementation of out of hospital TOR but existing literature on EMS provider perceptions is limited. We sought to identify EMS providers' perceived barriers to performing out-of-hospital TOR in a large urban EMS system.Methods : The Chicago EMS System is a regional collaborative of EMS physicians, nurses and provider agencies, including the Chicago Fire Department (CFD), which provides exclusive emergency response for 9-1-1 calls in Chicago. CFD is an urban, fire-based EMS agency with a tiered response, with fire-fighter EMTs and paramedics providing initial care, and single role paramedics providing supplemental care and transport. A 2-page written survey was distributed to understand providers' experiences with managing OHCA and perceived barriers to TOR to inform subsequent improvements in protocol development and education.Results : Of 3500 EMS providers that received the survey, 2309 were completed (66%). Survey respondent demographics were fire-fighter/EMTB (69%), fire-fighter/paramedic (14%), and single role paramedic (17%). The most frequent barrier to field TOR was scene safety (86%). The most common safety issue identified was family reaction to TOR (68%) and many providers felt threatened by family when trying to perform TOR (38%). Providers with a higher career numbers of OHCA were more likely to have felt threatened by the family (OR 6.70, 95% CI 2.99–15.00) and single role paramedics were more likely than FF/EMTBs to have felt threatened (OR 3.34, 95% CI 2.65–4.22). Barriers to delivering a death notification after TOR, include being uncomfortable or threatened with possible family reaction (52%) and family asking to continue the resuscitation (45%). There was lack of formal prior death notification training, the majority learned from colleagues through on the job training.Conclusions : Our study identifies scene safety, death notification delivery, and lack of formal training in death notification as barriers that EMS providers face while performing TOR in a large urban EMS system. These findings informed educational and operational initiatives to overcome the identified provider level issues and improve compliance with TOR policies.